2016
DOI: 10.1186/s40170-016-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid desaturation is detrimental to cancer cell survival in metabolically compromised environments

Abstract: BackgroundEnhanced macromolecule biosynthesis is integral to growth and proliferation of cancer cells. Lipid biosynthesis has been predicted to be an essential process in cancer cells. However, it is unclear which enzymes within this pathway offer the best selectivity for cancer cells and could be suitable therapeutic targets.ResultsUsing functional genomics, we identified stearoyl-CoA desaturase (SCD), an enzyme that controls synthesis of unsaturated fatty acids, as essential in breast and prostate cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
184
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(199 citation statements)
references
References 45 publications
(63 reference statements)
11
184
0
4
Order By: Relevance
“…A study on fatty acid compositions of phospholipids in mucosal gastric cancer cells also indicated that omega-6 fatty acid has a higher percentage compared with those of normal tissue due to the higher concentration of arachidonic acid [28]. It seems unsaturated fatty acids inhibit the apoptosis process in breast and prostate cancer [26]. The previous findings were consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study on fatty acid compositions of phospholipids in mucosal gastric cancer cells also indicated that omega-6 fatty acid has a higher percentage compared with those of normal tissue due to the higher concentration of arachidonic acid [28]. It seems unsaturated fatty acids inhibit the apoptosis process in breast and prostate cancer [26]. The previous findings were consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Another study has represent that omega-3 and omega-6 fatty acids induced apoptosis in colon cancer cells through a mitochondrial pathway, activation of caspase-3 and -9, and inhibiting Bcl2 [25]. A study on stomach cancer cell line indicated that omega-3 fatty acid inhibited tumor growth and induced apoptosis in these cells [26]. Therefore, PUFAs are potent biological compounds that can prevent the growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from jejunum and ileum samples was isolated from liquid nitrogen frozen and ground tissues with TRIZOL regent (Invitrogen, USA) and then treated with DNase I (Invitrogen, USA) [21-23]. The reverse transcription was conducted at 37°C for 15 min, 95°C 5 sec.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction with oncogenic signaling pathways supports lipid metabolism as a suitable target for anti-cancer therapy. Furthermore, multiple earlier publications reported the universal effectiveness of SCD1 inhibition in limiting the growth of cancer cells of various origins including lung, breast, prostate, and colon (12,13). Most significant was the observation that SCD1 and lipid desaturation were required for the formation and growth of cancer spheroids or xenograft tumors (8,12).…”
mentioning
confidence: 98%
“…Furthermore, multiple earlier publications reported the universal effectiveness of SCD1 inhibition in limiting the growth of cancer cells of various origins including lung, breast, prostate, and colon (12,13). Most significant was the observation that SCD1 and lipid desaturation were required for the formation and growth of cancer spheroids or xenograft tumors (8,12). This observation supports the Editorial Observation-driven inquiry: Raman spectroscopic imaging illuminates cancer lipid metabolism Aurelio Lorico 1 theory of re-activation of de novo lipogenesis in solid tumors as part of cancer metabolic reprogramming.…”
mentioning
confidence: 99%